PENGEMBANGAN KOMIK DIGITAL INTERAKTIF BERBASIS AUDIOVISUAL PADA MATA PELAJARAN BAHASA INDONESIA UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS VI SDN 09 PAGI DUREN TIGA JAKARTA - Aufa, Tazkia Amalia; Yuli Satriyani, Febrianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Elementary school students’ reading comprehension skills remain relatively low due to the use of learning media that lack variation and are dominated by text without attractive visual and audio support. This condition was also found among sixth-grade students at SDN 09 Pagi Duren Tiga Jakarta, where some students had not yet met the Minimum Mastery Criteria in Indonesian language learning. This study aimed to develop an interactive audiovisual-based digital comic and to examine its feasibility and effectiveness in improving students’ reading comprehension skills. The study employed a Research and Development (R&D) method using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were sixth-grade students at SDN 09 Pagi Duren Tiga Jakarta. Data were collected through observation, interviews, expert validation questionnaires, and pretest–posttest tests. The results showed that the interactive audiovisual-based digital comic was considered feasible based on expert evaluations. Furthermore, the effectiveness test indicated an improvement in students’ reading comprehension skills, as shown by higher posttest scores compared to pretest scores and N-Gain results in the moderate to high categories. Therefore, the interactive audiovisual-based digital comic is effective as a learning medium for improving reading comprehension skills in elementary school Indonesian language learning.